Cut-off grade determination for the maximum value of a small Wits-type gold mining operation (The Southern African Institute of Mining and Metallurgy, 2003)
Work undertaken in the field of cut-off grade optimization has not advanced much beyond the work undertaken by Lane in 1988. His definitive work is based on the calculus of the Net Present Value criterion which is the most widely understood, consistent, and appropriate method by which sequential cash flows arising from the extraction of mineral reserves from an exhaustible resource can be represented. Although the mathematics is not complex Lane’s method is not a widely appreciated or applied approach to maximizing the value of a mining operation through selection and balancing of operational cut-off grades. Three stages in a mining operation namely, mining, processing and marketing were defined by Lane and the economics of each stage are identified and isolated to provide an optimum cut-off for each stage. Points of intersection along the present value curves for each stage of a mining operation are used to identify balancing cut-off grades at points where the capacity of the mining, processing and marketing stages is fully utilized and the Net Present Value of the operation is optimized. Data that simulate a small, deep-level Witwatersrand-type gold mine with an average grade of 6 g/t Au and a logrithmic variance of 1.2,are applied to the model to illustrate the benefits of representing cut-off grades in terms of present value curves for different segments of a mining operation. Keywords: Cut-off grade, Net Present Value, grade-tonnage curve, balancing cut-off grade, mining, processing, marketing.